2007
DOI: 10.1021/ac071102b
|View full text |Cite
|
Sign up to set email alerts
|

A General, Positive Ion Mode ESI-MS Approach for the Analysis of Singly Charged Inorganic and Organic Anions Using a Dicationic Reagent

Abstract: Anion analysis continues to be of great importance to many scientific and technical fields. We propose here a general and sensitive method of detecting singly charged anions by ESI-MS and LC-ESI-MS as positive ions. This method utilizes a dicationic reagent to form a complex with the anion that retains an overall positive charge for analysis by MS. Nitrate, thiocyanate, perchlorate, perfluorooctanoic acid (PFOA), halogenated acetic acids, and various other inorganic and organic anions and are investigated. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
133
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(137 citation statements)
references
References 63 publications
3
133
1
Order By: Relevance
“…Phenyl phosphate had lower LODs than hydrogen phosphite. This result is in general agreement with earlier work that used dicationic reagents and singly charged anions, which found that more oxidized species had better LODs [42].…”
Section: Resultssupporting
confidence: 93%
“…Phenyl phosphate had lower LODs than hydrogen phosphite. This result is in general agreement with earlier work that used dicationic reagents and singly charged anions, which found that more oxidized species had better LODs [42].…”
Section: Resultssupporting
confidence: 93%
“…As for F -, the LOD value shows that Al 3+ affords better detection performance than In 3+ in accordance with the stability of the Al-and In-F complexes in aqueous solution: log K1 = 6.13 for Al-F, and 3.70 for In-F. 40 The LOD value for Cl -was higher than those for Br -and I -, and this was considered to be mainly due to Clcontamination. The LOD values for Cl -(0.32 ng in 30 mm 3 ), Br -(9.1 pg) and I -(6.1 pg) listed in Table 5, were, however, much lower than conventional methods, such as IC, ISE, and solution spectrophotometry, 41,42 being comparable to those of ESI tandem mass spectrometry (ESI-MS/MS), [31][32][33] and capillary electrophoresis (CE).…”
Section: Quantification Of Halides and Cyanide Ionsmentioning
confidence: 91%
“…Based on Ternary Complex Formation 7,14 3·1 Determination of ternary complex of halides, metal and APC So far, several techniques have been reported for the determination of halide anions by ESI-MS. [30][31][32][33] A direct determination of halide anions with an LOD of about 1 ppb has been reported, but a strong interference was observed due to the matrix effect. 30 The determination of inorganic anions as well as halides as ion-pairs with organic dications was studied by Armstrong, Dasgupta, and coworkers.…”
Section: Quantification Of Halides and Cyanide Ionsmentioning
confidence: 99%
See 2 more Smart Citations